Construction of a manipulator with six degrees of freedom and a rotary platform differentially pumped via retractable welded bellows. (November 2015) - Yuh, Jih-Young; Cheng, Cheng-Maw
Abstract: Photoelectron spectra (PES) have played an important role since the beginning of research in surface and material science. When these techniques are applied for the analysis of a more complicated system such as: highly correlated, surface-interface, transition-metal-oxide, samples are maneuvered between UHV chambers for sputtering, deposition or cleavage with a multiple-degree-of-freedom manipulator that consists of an x-y-z translational stage as well as rotation about these three axis. After these processes, a sample surface must be annealed to re-crystallize or cooled to its critical temperature before studying; control of temperature over a wide range is thus also an essential capability of a manipulator system. To integrate all above functions, a sample manipulator was constructed featuring control of temperature over a wide range -- 20 K to 1000 K, six degrees of freedom for sample positioning, sample transfer with exchangeable sample-mounting modules to fulfill varied experimental needs. Another special feature of our design is a retractable welded bellows to replace the formed bellows that connects to the differentially pumped rotary platform (DPRP) that provide the rotational motion of the sample in polar angular directions. This modification prevents the long formed bellows connected to its pumping system from dangling around the analysis vacuum chamber and interfering with other instruments. Highlights: A new sealing method between copper and stainless steel. A formed-bellows-free differentially pumped rotary platform. A welded bellows that functioned as a buffer of the cryogenic contraction. Samples can tilt from +20° to −15°, rotate 360° in polar and azimuthal direction. Coincidence of all rotation centers on the sample near one point in space.